Science and Development in Thai and South Asian Buddhism - Gosling, David L (Routledge Contemporary Southeast Asia Ser., 2019)
Cover -- Half Title -- Series Page -- Title -- Copyright -- Dedication -- Contents -- List of figures -- List of tables -- Preface -- Acknowledgements -- Glossary -- 1 Introduction -- SECTION A Buddhism in transition -- 2 Thai Buddhism in transition -- 3 New directions in Thai Buddhism -- 4 Visions of salvation: a Thai Buddhist experience of ecumenism -- 5 The changing roles of Thailand's lay nuns (mae chii) -- SECTION B Monastic development activities -- 6 Thai monks in rural development -- 7 Biogas for Thailand's rural development: transferring the technology -- 8 Urban Thai Buddhist attitudes to development -- 9 Redefining the Sangha's role in Northern Thailand: an investigation of monastic careers at five Chiang Mai wats -- 10 Buddhism for peace -- SECTION C Aspects of development and science -- 11 Thailand's bare-headed doctors -- 12 Thailand's bare-headed doctors: Thai monks in rural healthcare -- 13 Thai monks and lay nuns (mae chii) in urban health care -- 14 The scientific and religious beliefs of Thai scientists and their interrelationship -- 15 Embodiment and rebirth in the Buddhist and Hindu traditions -- Appendix -- Bibliography -- Index.